KOMUNIKASI WALI KELAS DENGAN ORANG TUA SISWA DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI SMA SEMESTA BILINGUAL BOARDING SCHOOL SEMARANG - Hasan Comce, Murniati AR, Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
ABSTRACT: Harmonious communication between homeroom teacher and parents is one of the factors that affect student achievement. With today's advanced communication techniques by establishing better communication can be obtained better results. This study aims to describe the program of homeroom teacher communication with parents, strategies used, obstacles faced and efforts are used to deal with obstacles to improve student achievements in Semesta Bilingual Boarding High School Semarang. The method used in this research is descriptive method with qualitative approach. Data collection techniques used were observation, interviews and documentation. Subjects of the research are homeroom teacher and parents of class XII, Principal, Head of Dormitory and Counselor of Semesta Bilingual Boarding High School Semarang. Research conducted in Semesta Bilingual Boarding High School environment with the population of 131 12th grade students of Semesta Bilingual Boarding High School. The results showed that: 1) Among the communication programs that made by school to establish better relationship between homeroom teachers and parents are  mother class program, club activities, guidance service, leadership, and the Student Information System. Programs that have been implemented have positive impact on student achievement, 2) among strategies of communication between homeroom teacher and parents to improve learning achievement of student are open house, home visit, social media, mother club, and discussion programs. With these strategies positive effect was seen on student achievement,. 3) obstacles that have been discovered are difference in perception, culture, basic character, poor choice of communication channel and no feedback. These obstacles have negative impact on student achievement, 4) efforts being done to overcome the obstacles that experienced are establishing two-way communication, making new rules, socialization, and more intensive meetings.KEYWORDS: communication, student achievement, homeroom teacher,parentst ABSTRAK: Komunikasi yang harmonis antara wali kelas dengan orang tua merupakan salah satu faktor yang mempengaruhi prestasi belajar siswa. Dengan teknik komunikasi yang canggih saat ini dengan membangun komunikasi yang lebih baik dapat diperoleh hasil yang lebih baik. Penelitian ini bertujuan untuk mengambarkan program komunikasi wali kelas dengan orang tua siswa, strategi komunikasi yang digunakan, serta hambatan-hambatan yang dihadapi dan upaya-upaya yang dilakukan untuk menghadapi hambatan-hambatan dalam meningkatkan prestasi belajar di SMA Semesta Bilingual Boarding School Semarang. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Subjek penelitian adalah wali kelas dan orang tua kelas XII , Kepala Sekolah, Kepala Asrama, dan Konselor SMA Semesta Bilingual Boarding School Semarang. Penelitian dilakukan di lingkungan SMA Semesta Bilingual Boarding School Semarang dengan populasi penelitian ini adalah siswa kelas XII SMA Semesta Bilingual Boarding School dengan jumlah 131 siswa. Hasil penelitian menunjukkan bahwa: 1) program komunikasi wali kelas dengan orang tua siswa diantaranya program ibu kelas, kegiatan klub, pembinaan, kepemimpinan, dan Sistem Informasi Siswa. Dari program yang telah dilaksanakan terlihat ada dampak yang positif terhadap prestasi belajar siswa, 2) strategi komunikasi wali kelas dengan orang tua siswa dalam meningkatkan prestasi belajar diantaranya open house, home visit, social media, mother club, dan program diskusi. Dengan strategi-strategi ini berdampak positif terhadap prestasi belajar siswa, 3) hambatan-hambatan yang sudah ditemukan adalah perbedaan persepsi, budaya, karakter dasar, poor choice of communication channel, no feedback, dengan hambatan-hambatan ini berdampak prestasi siswa sulit dicapai, 4) upaya-upaya yang dilakukan untuk mengadakan two way communication dengan membuat peraturan, sosialisasi, dan pertemuan yang lebih intensif.KATA KUNCI:  komunikasi, prestasi belajar, wali kelas, orang tua